Graded challenge in an aciclovir allergic patient. Issue 3 (1st June 2001) - Kawsar, M; Parkin, J M; Forster, G
Abstract : An immunocompetent woman presented with a hypersensitivity skin reaction following suppressive therapy with aciclovir for recurrent culture proved genital herpes simplex virus infection. She developed a similar reaction when treatment was changed to famciclovir. Without antiviral suppression her recurrences were frequent and distressing. Graded challenge was performed and she became tolerant to aciclovir. She successfully continued suppressive therapy for 1 year with no further hypersensitivity reactions or recurrences.